The Reflective-Stimulation Leadership Model to Reduce Bullying in Islamic Junior High Schools - Nuraeni, Iis; Subasman, Iman; Widiantari, Dian; Muttaqin, Muhammad Azhar (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Bullying remains a persistent issue in Islamic educational institutions, threatening both student well-being and the cultivation of character values. This study examines the application of the Reflective-Stimulation Leadership Model, which integrates the intellectual stimulation dimension of transformational leadership with the reflective dimension of spiritual leadership. Using a qualitative case study and phenomenological approach, data were collected through observation, semi-structured interviews, open-ended questionnaires, and document analysis. The research involved the school principal as the primary subject, supported by data from counselors, homeroom teachers, and students. Findings show that the principal implemented reflective dialogue, role modeling, value-based educational strategies, and participatory forums such as